Developmental Dysplasia of the Hip: A Review of Etiopathogenesis, Risk Factors, and Genetic Aspects - Stefan Harsanyi; Radoslav Zamborsky; Lubica Krajciova; Milan Kokavec; Lubos Danisovic (Medicina, 2020)
As one of the most frequent skeletal anomalies, developmental dysplasia of the hip (DDH) is characterized by a considerable range of pathology, from minor laxity of ligaments in the hip joint to complete luxation. Multifactorial etiology, of which the candidate genes have been studied the most, poses a challenge in understanding this disorder. Candidate gene association studies (CGASs) along with genome-wide association studies (GWASs) and genome-wide linkage analyses (GWLAs) have found numerous genes and loci with susceptible DDH association. Studies put major importance on candidate genes associated with the formation of connective tissue (COL1A1), osteogenesis (PAPPA2, GDF5), chondrogenesis (UQCC1, ASPN) and cell growth, proliferation and differentiation (TGFB1). Recent studies show that epigenetic factors, such as DNA methylation affect gene expression and therefore could play an important role in DDH pathogenesis. This paper reviews all existing risk factors affecting DDH incidence, along with candidate genes associated with genetic or epigenetic etiology of DDH in various studies.